Self-Assessment of Dental Anxiety in Patients Visiting Comprehensive Rural Health Service Project, Ballabgarh - Anindya Bhalla; Sukriti Bhalla Singh; . Sujata; Ashish Singh; Ajay Choudhary (Highlights on Medicine and Medical Research Vol. 12, 2021)
Aims: The purpose of this study was to estimate the prevalence, severity and associations of dental anxiety in a sample of the adult population visiting comprehensive Rural Health Service Department, Ballabgarh, Haryana. Dental anxiety is a common problem both for dental practitioners and the people. Settings and Design: The study was conducted in CRHSP Ballabgarh, Faridabad .The study was conducted in 5 weeks duration. Questionnaire based study was done using closed ended MODIFIED DENTAL ANXIETY SCALE (MDAS) questionnaire. Methods and Material: A sample of 379 adults (age ranging between 15 to 60 years; mean age male = 35.89 ± 14.10 and female 35.01 ± 12.38). The Modified Dental Anxiety Scale (MDAS) is a brief, self-complete questionnaire consisting of five questions (Q1 to Q5) and summed together to produce a total score ranging from 1 to 5. Statistical Analysis Used: SSP version 16 software, the percentage, means and standard deviation. Results: The results revealed that females were more apprehensive, compare to men. Based on distribution of anxiety according to age group, males between the age group 15 to 23 and 24 to 33 belonged fairly anxious group and only slight anxiety was observed in higher age group (44 to 53 yr). On the other hand, females were found to be very anxious at higher age group of 24-33 and 34-43. Conclusions: It is recommended that dental education and health care services should be promoted to overcome the fear and anxiety factor.